PENILAIAN AUTENTIK MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SMP NEGERI 4 PARIAMAN - Novialdi Putra (al-fikrah: Jurnal Manajemen Pendidikan, 2016)
A qualitative study was conducted at investigating the implementation of authentic assessment in curriculum 2013 on Islamic education and attitude of SMP Negeri 4 Pariaman and the factors supporting and inhibiting the authentic assessment. This study applied observation, interview, and documentation. The results showed that the implementation of authentic assessment was run well. The assessment upgraded the students’ interest and students’ creative. The assessment also increased students’ motivation on activities were done in school environment. The factor supported the implementation of authentic assessment was workshop and infrastucture while the factor inhibitted the implementation was too many students in the class. Keywords: Authentic Assessment, Curriculum 2013, Islamic Education, Attitude, SMP